Tinjauan Al-Qur’an Terhadap Kesetaraan Gender Dalam Pembagian Warisan - Taufiqurrahman fauzi; Mohammad Ruslan (El-Furqania : Jurnal Ushuluddin dan Ilmu-Ilmu Keislaman, 2022)
Problems among the people never stop at one time. Although these problems have been raised by the salaf scholars. As was the case a few years ago, there was a lot of discussion about the difference in inheritance provisions of 2:1 for boys and girls which were considered unfair by feminists. Starting from this problem, the author took the initiative to thoroughly discuss how according to the Qur'an, and whether the 2:1 division can be said to be fair. To answer this issue, the researchers used a qualitative approach with content analysis data analysis techniques. From the results of this study indicate that: The distribution of inheritance as determined by the Qur'an in Surah al-Nisa' Verse 11, for boys and girls includes an unequal distribution because the division of inheritance listed in Surah al-Nisa ' In verse 11, the boy gets a 2:1 share or in other words the boy gets a share that is double that of the girl. Justice Division 2: 1 due to several things including the burden of the son is greater and the son is obliged to provide for his wealth to his family. Keywords: al-Qur'an, equality, gender, inheritance